The Development of a Highly Informative Mouse Simple Sequence Length Polymorphism (SSLP) Marker Set and Construction of a Mouse Family Tree Using Parsimony Analysis - Witmer, Philip D.; Doheny, Kimberly F.; Adams, Marcia K.; Boehm, Corinne D.; Dizon, Jane S.; Goldstein, Janet L.; Templeton, Tira M.; Wheaton, Ariana M.; Dong, Penny N.; Pugh, Elizabeth W.; Nussbaum, Robert L.; Hunter, Kent; et al. (Genome Research, 2003)
To identify highly informative markers for a large number of commonly employed murine crosses, we selected a subset of the extant mouse simple sequence length polymorphism (SSLP) marker set for further development. Primer pairs for 314 SSLP markers were designed and typed against 54 inbred mouse strains. We designed new PCR primer sequences for the markers selected for multiplexing using the fluorescent dyes FAM, VIC, NED, and ROX. The number of informative markers for C57BL/6J × DBA/2J is 217, with an average spacing of 6.8 centiMorgans (cM). For all other pairs of strains, the mean number of informative markers per cross is 197.0 (SD 37.8) with a mean distance between markers of 6.8 cM (SD 1.1). To confirm map positions of the 224 markers in our set that are polymorphic between Mus musculusand Mus spretus, we used The Jackson Laboratory (TJL) interspecific backcross mapping panel (TJL BSS); 168 (75%) of these markers had not been previously mapped in this cross by other investigators, adding new information to this community map resource. With this large data set, we sought to reconstruct a phylogenetic history of the laboratory mouse using Wagner parsimony analysis. Our results are largely congruent with the known history of inbred mouse strains.[The following individuals kindly provided reagents, samples, or unpublished information as indicated in the paper: E. Eicher, T. Golovkina, J. Cheverud, S. Cropp, P. Denny, and A. Southwell.]